KOMPETENSI GURU DALAM PERSFEKTIF PERUNDANG - UNDANGAN - ., Hasnawati (Inspiratif Pendidikan, 2020)
Teacher competence is the ability of a teacher to do duties responsibly and properly. Competence is the ability and authority of teachers to carry out their teaching profession. Teacher competence is also the skill or ability possessed by teachers regulated in Law Number 14 in 2005 concerning Teachers and Lecturers, Ministry of Education Number 16 in 2007, and Government Regulation Number 74 in 2008. Teacher competency standards is a set of knowledge, skills and behaviors that must be possessed, comprehended, mastered, and actualized by the teacher to fulfill their professional duty. Teacher competences as referred to article (1) PP 74/2008 include pedagogical, personal, social, and professional competences obtained through professional education. These four teacher competences are holistic which means whole integrated and interrelated. Specifically for PAI (Islamic education) teachers, based on regulation of Religion Ministry Number 16 in 2010 Article 16, there is an additional competency namely leadership.